Acetylation of Lysine 564 Adjacent to the C-terminal Binding Protein-binding Motif in EVI1 Is Crucial for Transcriptional Activation of GATA2 - Shimahara, Akiko (American Society for Biochemistry and Molecular Biology, 2010)
Ecotropic viral integration site 1 (EVI1) is an important transcription factor for leukemogenesis. EVI1 is a member of a group of transcription factors with C-terminal binding protein (CtBP)-binding motifs that act as transcriptional co-repressors; however, we recently found that EVI1 directly activates GATA2 transcription, which is an important gene for the maintenance of hematopoietic stem cells. We show here that EVI1-activated GATA2 transcripts derive from exon 1S of GATA2, which is specifically activated in neural and hematopoietic cells. EVI1 was acetylated by the histone acetyltransferase p300/CBP association factor (P/CAF) in myeloid leukemia cells and hematopoietic progenitor cells. Acetylation at Lys(564), which is adjacent to the CtBP-binding consensus sequence of EVI1, was found to be important for transcriptional activation of GATA2. Mutation of Lys(564) to alanine (K564A) markedly reduced the ability of EVI1 to bind DNA and activate transcription of GATA2. Furthermore, we confirmed that Lys(564) in EVI1 was specifically acetylated in leukemia and primary hematopoietic cells by using an antibody directed against an acetylated Lys(564) EVI1 peptide. Moreover, co-transfection of P/CAF with EVI1 overcame the suppressive effect of the CtBP co-repressor and resulted in GATA2 transcriptional activation; nonetheless, CtBP2 was still included in the protein complex with EVI1 and P/CAF on the EVI1-binding site in the GATA2 promoter region. Thus, acetylation of EVI1 at Lys(564) by P/CAF enhances the DNA binding capacity of EVI1 and thereby contributes to the activation of GATA2.